A meta-analysis on promotion- and prevention-focused job crafting. Issue 1 (2nd January 2019) - Lichtenthaler, Philipp W.; Fischbach, Andrea
ABSTRACT: The purpose of this study is to present a meta-analytical summary of the job crafting literature. We integrate resource- and role-based job crafting conceptualizations in one job crafting model, which can theoretically account for beneficial and detrimental job crafting effects. Applying reasoning from regulatory focus theory we differentiated promotion-focused (increasing job resources and challenging job demands; expansion-oriented task, relational, and cognitive crafting) from prevention-focused (decreasing hindering job demands; contraction-oriented task and relational crafting) job crafting. We hypothesized that promotion-focused job crafting relates positively and prevention-focused job crafting relates negatively with employee health, motivation, and performance. Results of cross-sectional meta-analytical structural equation modelling showed that promotion-focused job crafting was positively related with work engagement and negatively related with burnout, while prevention-focused job crafting was negatively related with work engagement and positively related with burnout. Moreover, promotion-focused job crafting was positively and prevention-focused job crafting was negatively related with performance through work engagement and burnout. Results of longitudinal meta-analytical structural equation modelling showed that there were reciprocal, positive relationships between promotion-focused job crafting and work engagement, and between prevention-focused job crafting and burnout. Implications for future research and practice are discussed.